(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Coronavirus disease 2019 (COVID-19) is the present global public health problem that has already caused pandemic since 2020. This respiratory corona viral infection can cause severe respiratory illness and death might be the outcome in severe cases. COVID-19 can manifest several atypical clinical presentations including neurological presentation. An important neurological problem is neurovascular thrombotic disorder A thrombotic event might be due to arterial or venous system affection. The study was conducted in the public laboratories on the outskirts of Baghdad after collecting 100 samples, (60) of people infected with Covid - 19 and (40) of healthy people and the ages of the people ranged from 18-80 years and the ages of the healthy ones from 18-70 years old. The study was conducted to investigate some biochemical indicators which includes Chemokine CXCL10, Fibrinogen, D-dimer, ferritin, C-reactive protein, iron and fibrinogen. The results showed a significant increase in the level of the chemokine CXCL10 in patients infected with Covid-19 virus compared to the control group, and a significant increase in the levels of D-dimer, ferritin, C-reactive protein, iron and fibrinogen which are important biochemical indicators in Covid – 19 patients.